ظاهرة انتشار الأحاديث المردودة بين المجتمع الماليزي: أسباب وحلول: Dissemination of Rejected Hadith among The Malaysian Society: Causes and Solutions - Nur Afifi Alit; Shumsudin Yabi (RABBANICA - Journal of Revealed Knowledge, 2023)
The dissemination of rejected hadith has been a continuous challenge since the emergence of hadith literature in the 19th century. There are several reasons behind this phenomenon which, if not treated seriously, can hinder the search for appropriate solutions because Muslims depend highly on these hadith in their daily worship. Therefore, this study is conducted to identify the cause of this phenomenon and find an appropriate solution. The methods used in this qualitative study are document analysis, supported by observations of the occurring phenomena, and the documents gathered are later analyzed using the descriptive method. This study found external and internal causes that assisted in spreading these hadith in society, pointing to two main parties as the spreaders of hadith: the preachers and the intellectuals. In addition, this study also suggests taking advantage of the enhancement of technology, like television programs and mobile applications, to educate society on hadith knowledge and the difference between accepted and rejected hadith. Finally, it is also suggested that all parties and bodies in Malaysia related to this matter should be gathered to address this issue with their best foot forward to achieve the best solutions. تُعدّ التَّسَرُّبُات الدَّخيلة المتمثِّلة في انتشار الأحاديث المردودة في المجتمع الماليزي من الإشكالات المتعاقبة منذ بذور المصنَّفات الحديثية في أرخبيل الملايوي في القرن التاسع عشر الميلادي. وحقيقة، فإن لهذه الظَّاهرة أسباب متعدِّدة، وإن لم تعالج بجد؛ سيصعب البحث عن الإجراءات الوقائية المرغوبة؛ نظرًا لركون المسلمين إلى تلك الأحاديث في عباداتهم اليومية. وعلى هذا، هدفت الدراسة إلى التعرُّف على الأسباب المؤدِّية إلى هذه الظَّاهرة التي تساعد في انتشارها بطريقة أسرع بين المجتمع. وكذلك حاول البحث وضع الحلول المناسبة التي تمس المساهمات المتاحة لدى الفئات المسؤولة سواء من طرف الحكومة أو المؤسسات الأهلية. واستخدم الباحث منهج تحليل الوثائق لجمع البيانات المناسبة مع طبيعة الدِّراسة، مع الاستعانة بملاحظة وقائع الظَّاهرة، قبل القيام بتحليلها مستخدمًا المنهج الوصفي. وأظهرت نتائج الدِّراسة على اشتمال تلك الأسباب على الخارجي والداخلي منها، بحيث ترجع الدَّاخلية إلى ناقلي الأحاديث من الدُعاة والمثقّفين، ومتلقِّيها من عوام المسلمين المنتفعين بها. وكذلك اقترحت الدراسة أن تكون الحلول الممكنة لمعالجة تلك الظاهرة باستغلال التكنولوجيا الحديثة من الوسائل المعاصرة في نقل المعلومات مثل البرامج التلفزيونية، وكذلك برامج الهواتف الذكية في تقريب علوم الحديث إلى المجتمع إبرازا لدورها المهم في التمييز بين الصحيح والضعيف من الحديث، إضافة إلى القيام بتكريث القوى الوافرة لدى الجهات ذات الاهتمام بهذه القضية للوصول إلى الحلول الفعّالة.